The relationship between BRAF genetic alterations and the risk of tumour recurrence in Pilocytic Astrocytomas in children diagnosed at Red Cross Children's Hospital over a 33-year period - Viljoen, Nandi (Department of Clinical Laboratory Sciences, 2024)
Introduction: Pilocytic astrocytomas (PAs), glial-derived neoplasms, are the most common central nervous system (CNS) tumours reported in the paediatric population. 1 PAs are circumscribed astrocytic gliomas associated with a favourable overall survival and thus regarded as low grade by the World Health Organisation (WHO), with a reported five-year survival rate between 75% to 100%. 2,3 Optimal treatment of partially resected, deep anatomic location and recurrent tumours are challenging. Over the past decades, PAs have been the object of an increasing number of molecular studies which tried to identify favourable and unfavourable prognostic factors. Essentially all PAs harbour genetic aberrations resulting in the deregulation of the MAPK signalling pathway, with BRAF gene mutations being the most frequent. 4 However, reports on the impact of specific mutations on patient prognosis are controversial. 5–8 Advances in molecular techniques have opened the door for further studies to determine the relationship between these BRAF alterations (point mutations and gene fusions) and the risk of tumour recurrence. Purpose: The overall aim of this study was to determine if BRAF genetic alterations impact patient prognosis. This was done by evaluating the expression of BRAF using immunohistochemistry (IHC), fluorescence-in-situ hybridisation (FISH) and polymerase chain reaction (PCR) and comparing it to tumour recurrence. The results will also be compared to clinicopathological findings. Methods: Study design: A retrospective cohort laboratory-based study included all cases diagnosed with PAs that presented to Red Cross Children's Hospital (RCC) from January 1984 to December 2016. Patient selection and data collection: Convenient sampling was done by searching the electronic laboratory information database (Disa and NHLS TrakCare) of the Division of Anatomical Pathology for all cases diagnosed with PAs. Data collection included: age at diagnosis, tumour site, management and recurrence. Laboratory methods: Archived stained slides of all the cases were reviewed, the diagnosis was confirmed on histology, and tissue blocks were retrieved. The presence of BRAF genetic aberrations were examined using immunohistochemistry, FISH and PCR. Results: Sixty-nine paediatric patients with PAs were identified over the study period with a median age of 6 years. This included 33 females and 21 males (in 15 cases the gender was not documented). Most tumours (62.32%) were located in the cerebellum, followed by the cerebral hemisphere (18.84%). The tumour recurred in 21 individuals, of which 3 had incomplete surgical resections. 46.16% of supratentorial tumours recurred compared to a recurrence risk of only 20.93% in infratentorial tumours. BRAF immunohistochemistry was negative in all the cases, and FISH studies did not show BRAF rearrangements. Conclusion: The findings of this study were broadly consistent with published literature in terms of age at presentation, location of the tumour and tumour location concerning the risk of recurrence. While most studies revealed an equal or slight male predominance, this study showed that the tumour developed slightly more frequently in females. Our study did not find a correlation between the risk of recurrence and BRAF genetic aberrations.